Comparative efficacy of different antihypertensive drug classes for stroke prevention: A network meta-analysis of randomized controlled trials - Yu, Ding; Li, Jun-xia; Cheng, Yuan; Wang, Han-dong; Ma, Xin-di; Ding, Tao; Zhu, Zhong-ning (PLOS ONE, 2025)
Objective The study aimed to compare the effectiveness of various antihypertensive drugs in preventing strokes in hypertensive patients. Methods We conducted a comprehensive search of PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov to identify randomized controlled trials (RCTs) investigating the efficacy of antihypertensive drugs in stroke prevention from inception until April 2023. A network meta-analysis in a Bayesian framework was performed using the random-effects model. Results This study included 88 RCTs involving 487,076 patients to investigate the effects of antihypertensive drugs in preventing stroke. Among these trials, 58 RCTs specifically focused on comparing the impact of such drugs on hypertensive subjects. In overall population, Angiotensin-converting enzyme inhibitor (ACEIs), Angiotensin receptor blockers (ARBs), Calcium channel blockers (CCBs), and Diuretics (DIs) demonstrated superiority over placebo in in reducing stroke, all-cause mortality, and cardiovascular mortality. CCBs and DIs outperformed β adrenergic receptor blockers (BBs), ACEIs, and ARBs in stroke reduction. However, when focusing on hypertensive patients, ACEIs, CCBs, and DIs proved superior to placebo in reducing stroke, all-cause mortality, and cardiovascular mortality. ARBs reduced stroke and all-cause mortality but lacked efficacy in reducing cardiovascular mortality. Of the various CCB subclasses, only the Dihydropyridines displayed efficacy in preventing stroke, all-cause mortality, and cardiovascular mortality. Among diuretic subclasses, thiazide-type DIs exhibited no efficacy in preventing all-cause mortality. ACEIs+CCBs were more effective than ACEIs or ARBs monotherapy in reducing stroke, more effective than ACEIs, ARBs, CCBs, or DIs monotherapy in reducing all-cause mortality, and more effective than ARBs in reducing cardiovascular mortality. Conclusion These findings suggest that ACEIs, dihydropyridine CCBs, and thiazide-like diuretics may provide superior prevention against stroke, all-cause mortality, and cardiovascular mortality in hypertensive patients. Combinations of ACEIs and CCBs may provide enhanced protection of stroke than ACEIs or ARBs monotherapy.